2017
DOI: 10.1007/s11295-017-1138-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in bean morphology and biochemical composition measured in different genetic groups of arabica coffee (Coffea arabica L.)

Abstract: The narrow genetic base of commercial arabica resulting from intensive selection for quality during domestication and self-pollination has been well documented, raising the need for new diverse germplasm sources. Beans of 232 diverse arabica coffee accessions originating from 27 countries were harvested from the germplasm collection at CATIE, Costa Rica. Substantial variation was observed for bean morphology including 100 bean weight, bean length, width, thickness and bulk density. Non-volatiles including caff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
5
23
0
Order By: Relevance
“…The genetic diversity analysis using SNP markers revealed that the collection of C . arabica used in this study has a higher genetic diversity than traditional cultivars, consistent with the great phenotypic variability observed for the biochemical characterization previously reported 2 , 7 , 12 . In this context, our Ethiopian germplasm collection has been shown to be a valuable source of novel favorable biochemical characteristic-related alleles, which can be explored by breeding programs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The genetic diversity analysis using SNP markers revealed that the collection of C . arabica used in this study has a higher genetic diversity than traditional cultivars, consistent with the great phenotypic variability observed for the biochemical characterization previously reported 2 , 7 , 12 . In this context, our Ethiopian germplasm collection has been shown to be a valuable source of novel favorable biochemical characteristic-related alleles, which can be explored by breeding programs.…”
Section: Discussionsupporting
confidence: 90%
“…Although biochemical compounds related to beverage quality traits in coffee, including lipid and diterpene contents 2 , 7 , 12 , have been already described, this is the first large-scale study using an Arabica population that includes several wild accessions from Ethiopia. Accessions with different lipid and diterpene contents may serve as a source of alleles for the development of plants with desirable lipid and diterpene contents in the beans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, The W100 is widely used for other crops. For coffee, this measurement is used in some studies where it appears to be representative of the bean density and therefore of the quality of seed filling during the development and ripening of the fruit (Bertrand et al 2005;Tran et al 2017). Here, we studied the bean size and the weight of 100 healthy green beans.…”
Section: Discussionmentioning
confidence: 99%